Analysis of the Hospital Marketing Mix and Its Effect on Patient Loyalty in the Outpatient Department of Arjawinangun Regional General Hospital - Safitri, Zakiyah; Rumengan, Grace S; Yulius, Dicky; Wihartanti, Diah Vita (IJBLE Scientific Publications Community Inc., 2026)
This study aims to analyze the influence of the hospital marketing mix on patient loyalty at RSUD Arjawinangun, Cirebon Regency. Using a quantitative cross-sectional design, data were collected from 151 outpatient respondents through structured questionnaires. The marketing mix variables examined included product, price, place, promotion, people, process, and physical evidence. Data were analyzed using descriptive statistics, Chi-Square tests, and multivariate logistic regression with a forward stepwise method. The results of the bivariate analysis showed that price, place, promotion, people, process, and physical evidence were statistically significantly associated with patient loyalty (p < 0.05), whereas the product dimension was not. Multivariate analysis revealed that physical evidence, promotion, and people were the most dominant factors influencing patient loyalty, with the final model explaining 60.5% of the variance in loyalty. Patients who perceived hospital facilities as clean, comfortable, and well-organized, received clear and informative promotional communication, and experienced professional and empathetic services from hospital staff were significantly more likely to demonstrate high loyalty. These findings indicate that patient loyalty in public hospitals is shaped not only by clinical services but also by experiential and relational aspects of healthcare delivery. Therefore, hospital management should integrate service quality improvement, human resource development, and strategic promotion to enhance sustainable patient loyalty.